Inhibition of Cellular Protein Synthesis by Simultaneous Pretreatment of Host Cells with Fowl Plague Virus and Actinomycin D: a Method for Studying Early Protein Synthesis of Several RNA Viruses - Kaluza, G. (1976)
A method is described for analysis of viral protein synthesis early after infection when minute amounts of viral proteins are effectively concealed by large amounts of produced host-specific proteins. The method is superior to a radioimmune assay, since all virus-induced proteins can be measured independent of their immunological reactivity. Host-specific protein synthesis can be suppressed by infection with fowl plague virus. Addition of actinomycin D 1.25 h postinfection does not prevent this suppression, but it does block effectively the formation of fowl plague virus-specific proteins. Such cells synthesize only small amounts of cellular proteins, as revealed by polyacrylamide electrophoresis. They can be superinfected with several different enveloped viruses, however, without significant diminution of virus yields. In pretreated cells the eclipse is shortened for Semliki Forest virus, Sindbis virus, and vesicular stomatitis virus, but prolonged for Newcastle disease virus. The onset of protein synthesis, specific for the superinfecting virus, could be clearly demonstrated within 1 h after superinfection. At this time, in cells superinfected with Semliki Forest virus, great amounts of NSP 78 (nonstructural protein; molecular weight, 78 × 10(3)) and reduced amounts of the core protein C could be demonstrated. The precursor glycoprotein NSP 68 is followed by a new polypeptide, NSP 65; three proteins with molecular weights exceeding 100 × 10(3) were observed which are missing later in the infectious cycle. Similar results were obtained after superinfection with Sindbis virus. The formation of a new polypeptide with a molecular weight of about 80 × 10(3) was detected. After superinfection with vesicular stomatitis virus or Newcastle disease virus the formation of new proteins, characteristic for the early stage of infection, was not observed.